The electromagnetic spectrum : key to the universe - Branley, Franklyn M. (Mansfield), 1915- (Exploring our universe, 1979)
An explanation of the nature of the electromagnetic spectrum, the scientific investigations that led to our understanding of it, and its role as a tool of science.